Perancangan Dan Implementasi Sistem Informasi Laporan Keuangan Apotek Jati Jaya Dengan Menggunakan Bahasa Pemrograman PHP Dan Database MySQL - Yandri, Yandri (Journal of Computer Science and Information System(JCoInS), 2022)
The development of technology at this time continues to grow rapidly. This also has an impact on the development of the business world including trade. Tight business competition encourages every company to be more careful in determining the policies taken, so that fast, accurate and relevant information is needed to facilitate human work and minimize errors in every transaction activity. One of the problems that often arises is the incompatibility of financial statements with transactions that occur. To prevent errors in the processing of reports required an information system that has been computerized to facilitate the creation of reports supported by a basic method of accounting. With the computer can facilitate employees in managing the Financial Statement Information System. With this financial reporting system, the data will be stored in a database, so that the data is more structured and neatly arranged. With the Financial Reporting System can facilitate store employees in knowing the profit or loss.